Distribution, Source, and Burial of Sedimentary Organic Carbon in Kermadec and Atacama Trenches. Issue 5 (9th May 2021) - Xu, Yunping; Li, Xinxin; Luo, Min; Xiao, Wenjie; Fang, Jiasong; Rashid, Harunur; Peng, Yongbo; Li, Wenpeng; Wenzhöfer, Frank; Rowden, Ashley A.; Glud, Ronnie N.
Abstract: Knowledge of sedimentary organic carbon (OC) in hadal trenches, the deepest ocean realm, is rudimentary. Here, we conducted a comprehensive analysis of total OC (TOC), stable and radio‐carbon isotopes (δ 13 C and Δ 14 C), and biomarkers (e.g., n ‐alkanes, n ‐alkanols and n ‐fatty acids) in 12 sediment cores collected from hadal (trench axis) and non‐hadal (abyssal plains and slopes) settings of the Kermadec Trench (Southwestern Pacific) and Atacama Trench (Southeastern Pacific) regions. Our results show that the TOC in the Atacama Trench region (0.86% ± 0.69%) is significantly higher than that of the Kermadec Trench region (0.29% ± 0.08%), likely related to different surface primary productivity. In both trench regions, the hadal sites are generally characterized by more negative δ 13 C, higher TOC/TN ratio, and similar or higher abundance ratio of terrigenous/marine biomarkers as compared to the non‐hadal sites, suggesting the selective preservation of terrigenous biogenic/fossil OC at the hadal trench axis. The linear increase in 14 C age with sediment depth in non‐hadal cores reflects steady depositional conditions, whereas seven out of eight hadal sediment cores show 14 C age reversals presumably due to occasional mass‐transport deposits. Our results suggest (1) a strong heterogeneity in sedimentary OC characteristics between trenches and within each trench and (2) relatively high accumulation rates of terrigenous OC in both the Kermadec Trench (0.35 ± 0.04 g m −2 yr −1 ) and the Atacama Trench (1.4 ± 0.5 g m −2 yr −1 ). Thus, hadal trenches appear to represent an important environment for terrigenous carbon deposition in the deep ocean. Plain Language Summary: The hadal zone mainly composed of trenches is the deepest ocean realm with water depth over 6, 000 m. Due to the challenge of observation and sampling at the extreme depth, the hadal zone is one of the least explored ecosystems on Earth. Limited studies have suggested that hadal trenches have higher benthic biomass and microbial activity compared to surrounding abyssal plains, which has overturned a traditional view that the hadal zone is a "biological desert." Here, we conducted comprehensive geochemical analysis of sedimentary organic carbon in Kermadec Trench (Southwestern Pacific) and Atacama Trench (Southeastern Pacific). Our goal is to understand source, distribution, and burial of organic carbon that is an important food and energy source for benthic organisms in hadal trenches. We have obtained three key findings. (1) While extensive heterogeneity in sedimentary organic carbon in trench interior and between two trenches, the trench bottoms generally have higher fractional abundance of terrigenous organic carbon compared to surrounding abyssal/bathyal sites. (2) Mass‐transport deposits induced by episodic events (like earthquakes) profoundly influence organic carbon content and compositions in hadal trenches. (3) The hadal zone is an important but previously overlooked sink for terrigenous organic carbon in the deep ocean. Key Points: Sedimentary organic carbon (OC) reflects extensive variations among inter‐ and intra‐trenches More terrigenous OC was buried at hadal axis sites compared to non‐hadal sites The hadal zone is an important and previously overlooked sink for terrigenous OC in deep ocean